Studies on the ‘Aroor System of Sustainable Duck Rearing’ in Kerala, India - Abraham, John; Ravindran, Reghu (International Journal of Poultry Science, 2009)
A study on the duck rearing system for egg production existing in the coastal belt of Aroor region in Kerala state, India was carried out by means of structured questionnaire designed to collect data on socio-economic and husbandry factors affecting production. This system was unique in that the birds were fed on Fresh Prawn Waste (FPW), a waste product of prawn processing industry. The internal and external qualities of eggs laid by ducks fed on fresh prawn waste were compared with ordinary market eggs. The study revealed that this system was the most economical enterprise compared to any other animal husbandry enterprises in this region. The fresh prawn waste not only incorporates a salmon red colour to the yolk (due to the pigment xanthene) but also improves considerably the egg weight, albumen index, yolk index and shell quality. This system demonstrate how a waste product, which was causing lot of environment pollution can be effectively utilized to produce high quality balanced food, the eggs for human consumption economically.